Calcipotriol Plus Betamethasone Dipropionate Aerosol Foam For Scalp Psoriasis - Anderko M; Navarro Triviño FJ; Sharples CL (Dove Medical Press, 2019)
Marian Anderko,1 Francisco José Navarro Triviño,2 Charlotte L Sharples3 1Dermatologikum, Hamburg 20354, Germany; 2Dermatology and Venereology, Hospital Universitario San Cecilio, Granada 18016, Spain; 3LEO Pharma UK, Hurley, Berks, UKCorrespondence: Marian AnderkoDermatologikum, Stephansplatz 5, Hamburg 20354, GermanyTel +49 40 3510750Fax +49 40 35107510Email anderkomarian@gmail.comAbstract: This article presents real-world experience of the effectiveness of calcipotriol (50 μg/g)/betamethasone dipropionate (0.5 mg/g) (Cal/BD) aerosol foam formulation in three cases of scalp psoriasis, and briefly reviews the literature relating to Cal/BD topical therapy in adults with scalp psoriasis. Patients had long histories of scalp psoriasis and reported negative impacts on their lives (e.g. clothing choices, psychological well-being, employment status). Previous treatments had provided inadequate or only temporary relief. Cal/BD aerosol foam relieved itching in the first few days and was associated with visible improvement of flaky patches on the scalp at the end of the recommended 4-week treatment period. Controlled clinical trials in patients with scalp psoriasis are rare. There have been several trials in adults with scalp psoriasis involving Cal/BD gel or suspension scalp formulations, which have proven more effective and well tolerated compared with the individual components or vehicle alone. The Cal/BD aerosol formulation has enhanced skin penetration and higher bioavailability compared with the older formulations; studies show improved efficacy with Cal/BD aerosol foam, compared with older formulations, in patients with plaque psoriasis. The present cases confirm the benefits of Cal/BD aerosol foam in adults with scalp psoriasis, treated in real-world settings.Keywords: aerosol, betamethasone dipropionate, calcipotriol, psoriasis, scalp psoriasis